Using migratable objects to enhance fault tolerance schemes in supercomputers - Mendes, Celso; Meneses-Rojas, Esteban; Xiang, Ni; Gengbin, Zheng (IEEE Computer Society, 2015)
Supercomputers have seen an exponential increase in their size in the last two decades. Such a high growth rate is expected to take us to exascale in the timeframe 2018-2022. But, to bring a productive exascale environment about, it is necessary to focus on several key challenges. One of those challenges is fault tolerance. Machines at extreme scale will experience frequent failures and will require the system to avoid or overcome those failures. Various techniques have recently been developed to tolerate failures. The impact of these techniques and their scalability can be substantially enhanced by a parallel programming model called migratable objects. In this paper, we demonstrate how the migratable-objects model facilitates and improves several fault tolerance approaches. Our experimental results on thousands of cores suggest fault tolerance schemes based on migratable objects have low performance overhead and high scalability. Additionally, we present a performance model that predicts a significant benefit of using migratable objects to provide fault tolerance at extreme scale.
Keywords: Programación paralela, escalabilidad, resistencia; Propagación paralela; Escalabilidad; Research Subject Categories::TECHNOLOGY::Information technology::Computer science::Computer science